Hijrah Celebrity Creating New Religiosities, Branding Economics of Lifestyle in the Age of Muslim Mass Consumption - Lyansari, Kirana Nur (Analisis: Jurnal Studi Keislaman, 2018)
Much have been found in the research on the piety of the Indonesian Muslim communities in terms of ideology, culture and politics; the phenomenon of hijrah (internal conversion) among celebrities is not only limited to spiritual change but also in everyday of lifestyle economics. This paper examines three subjects of celebrities who write their hijrah stories drawing their secret transformation and telling their economic survive after hijrah. The three subjects are Riris Setyo Rini, Sakti personil group Sheila on 7 and Febrianti Almeera. Data gathered from the books published by each subject and some information of social media account of the subject concerned. Through examining the three subject, I argue that the hijrah process among certain celebrities have transformed from their psychological mindset while at the same time creating the new formation of lifestyle economics. This paper contributes to understand the new formation of religiosities in the context of mass Islamic consumption.